End-users, Public Services, and Industrial Relations: The Restructuring of Social Services in Ontario - Hickey, Robert (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2012)
SummaryThe global financial crisis beginning in 2008 resulted in a ballooning public debt and government efforts to constrain public expenditures. Responses to the financial crisis and its impact on human services in Ontario demonstrate the complex interactions across key actors – employers, government, unions, and family advocates. Building on previous scholarship which has explored the role of end-users as industrial relations actors (Bellemare, 2000; Kessler and Bach, 2011) this study deepens our understanding of the role and impact of end-users on the process and outcomes of industrial relations in the social services sector. The main contribution of the paper shows how end-users play unique and complex roles as industrial relations actors in Ontario’s developmental services sector. End-users have had a significant impact at three distinct levels of the industrial relations system (Bellemare, 2000). First, at the strategic level of public policy, in addition to the more traditional forms of grassroots lobbying, end-users have taken on formal roles in the governance network shaping public policy. The impacts of end-user advocacy have contributed to the significant transformation of the developmental services sector, including the closure of the remaining provincially-run institutions in 2009. Second, at the organizational level, end-users have displaced the traditional roles of employers. In some cases, this displacement has resulted in end-users operating as co-managers, with end-user management rights enshrined in collective agreements. In more significant ways, end-users have entirely replaced agency-based managers and become the employer of direct support staff. Third, end-users have driven changes at the level of the work process itself, going beyond the co-production of services, contributing to changes in the nature of direct support work. The work process has shifted from a focus on custodial care to more complex objectives of community development and social inclusion.